Technological quality, bioactive features, and glycemic index of gluten-free cakes formulated with lyophilized wild Prunus spinosa fruit - Cakir, Elif; Ozulku, Gorkem; Bekiroglu, Hatice; Arici, Muhammet; Sagdic, Osman (CODON PUBLICATIONS, 2024)
This study evaluated the effects of rice flour cakes enriched with wild fruit Prunus spinosa powder (PS) on technofunctional, nutrition, and eating quality. PS increases the cakes' ash, protein, and moisture values. Total phenolic content increased from 35.91 +/- 0.25 to 73.39 +/- 0.58 mg GAE g(-1), and gluten-free cakes' antioxidant capacity markedly increased with the increasing level of PS powder addition (p<0.05). The increase in PS decreased the glycemic index (eGI), and the lowest eGI was determined as 69.38 +/- 1.21 in cake samples containing 4% PS. Except for the 1% PS added sample, the increase in PS caused a decrease in specific volume, % porosity, and increase in hardness, including four days of storage. The addition of PS increased the redness (a*) and decreased the yellow (b*) and brightness (L*) values. The flow behavior index (n) of cake batters containing 1% and 2% PS were similar to the control group. Cakes containing 1% PS received the highest scores in sensory analysis. Although the increase in PS amount negatively affects the textural properties of gluten-free rice flour cakes, it is crucial to increase its bioactive properties and nutritional values and positively contribute to health by reducing the glycemic index.
Keywords: antioxidant; gluten-free cake; glycemic index; phenolic; Prunus spinosa; rice flour; RHEOLOGICAL PROPERTIES; PARTIAL REPLACEMENT; PHENOLIC-COMPOUNDS; POTENTIAL SOURCE; BATTER; FLOUR; L.; CAPACITY; MUFFINS; Food Science & Technology